The trial of the Gospel: An apologetic reading of Luke's trial narratives - Neagoe, Alexandru (Cambridge University, 2013)
For many years Luke-Acts has been studied as a work of history and theology. The Trial of the Gospel sets out to examine Luke's writings as an apologetic work, by focusing on those parts of Luke's story where the apologetic overtones seem most prominent - the trial narratives. By analysing the trials of all major Lukan characters - Jesus, Peter, Stephen, and Paul - Alexandru Neagoe argues that the narratives are best understood when viewed as part of Luke's apologia pro evangelio, a purpose which is in keeping with the author's declared aim to give his readers 'assurance' about the 'matters' in which they had been instructed (Luke 1.4). Neagoe concludes that the specific role of the trial narratives is to provide the framework within which important tenets of the Christian faith are themselves put 'on trial' before the reader, with the intended result of the gospel's confirmation